State of the Arctic Marine Biodiversity summary report; Key findings and advice on monitoring: 2017 - Conservation of Arctic Flora and Fauna (CAFF) (Arctic Council Secretariat, 2017)
The State of the Arctic Marine Biodiversity Report (SAMBR), is a product of the Circumpolar Biodiversity Monitoring Program (CMBP) of the ARctic Council's conservation of Arctic Flora and Fauna (CAFF) Working Group. By compiling available information, this report provides an important first step to identify knowledge gaps in circumpolar biodiversity monitoring efforts. Current biodiversity monitoring is not sufficient to describe the status and trends for many of the Focal Ecosystem Components (FEC): sea ice biota, plankton, benthos, fishes, seabirds and marine mammals. Snapshots of the state of knowledge and trends for each FEC are provided.